EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DENGAN GUIDED NOTE TAKING (GNT) PADA MATERI BANGUN RUANG DITINJAU DARI AKTIVITAS BELAJAR SISWA KELAS VIII SMP NEGERI Se-KABUPATEN KLATEN TAHUN PELAJARAN 2013/2014 - Dyah Susilawati; Budi Usodo; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstrac: The objective of this research was to investigate the effect of the learning models on the learning achievement in Mathematics viewed from learning activities of the students. The learning models compared were the Team Assisted Individualization (TAI) with Guided Note Taking (GNT) learning model, the Team Assisted Individualization (TAI) learning model, and conventional learning model. This research used the quasi experimental research method. Its population was all of the students in Grade VIII of state Junior Secondery  School of the Klaten regency in Academic Year 2013/2014. Instruments used to collect data were mathematics achievement test and the learning activities questionnaire. The data were analyzed using unbalanced two ways ANOVA. The results of the research are as follows. 1) The cooperative learning model of TAI with GNT result in a better learning achievement in Mathematics than the  cooperative learning model of TAI and the conventional learning model, whereas cooperative learning model of TAI result in the same good learning achievement in Mathematics as the learning model conventional. 2) The students with the high learning activities have the same good learning achievement in Mathematics as  the moderate learning activities. The students with the high and moderate learning activitiy have a better learning achievement in Mathematics than those with low learning activities. 3) In the cooperative learning model of TAI with GNT and TAI, the students with the high learning activities have the same good learning achievement in Mathematics as those with the moderate activities and the students with high and moderate learning activities have a better learning achievement in Mathematics than those with the low learning activities. In the conventional learning model, the students with high learning activities have the same good learning achievement in Mathematics as those with the moderate learning activities, whereas the high and moderate learning activities have a better learning achievement in Mathematics than those with the low learning activities. 4) For the students with the high and moderate learning activities, the cooperative learning model of TAI with GNT result in the same good learning achievement in Mathematics as the cooperative learning model of TAI and the conventional learning model. The student with the low learning activities, the cooperative learning model of TAI with GNT result in the same good learning achievement in Mathematics as the cooperative learning model of TAI, whereas the cooperative learning model of TAI with GNT and TAI result a better learning achievement in Mathematics than those the conventional learning model.Keywords: Team Assisted Individualization (TAI), Guided Note Taking (GNT), conventional learning, Learning Activities, Learning Mathematics Achievement